7-2(4-х) =-1 -3(х+5)=2х 12-3(х+4)=9 (х+4)-4(х+1)=1

yulyakarpenko3 yulyakarpenko3    2   25.06.2019 10:20    0

Ответы
mariach1 mariach1  20.07.2020 16:18
7-2(4-x) =-1
7-8+2x=-1
2x-1=-1
-1 и -1 сокращаются остаётся:
2x=0
x=0
ответ: 0

-3(x+5)=2x
-3x-15=2x
-3x-2x=15
-5x=15
x=-3
Ответ: -3

12-3(x+4)=9
12-3x-12=9
12 и -12 сокращаются остаётся:
-3x=9
x=-3
ответ: -3

(x+4)-4(x+1)=1
x+4-4x-4=1
4 и -4 сокращаются остаётся:
x-4x=1
-3x=1
x=- \frac{1}{3}
ответ: - \frac{1}{3}
ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Математика